Diffusion-weighted imaging for the differential diagnosis of disorders affecting the hippocampus - Förster, Alex; Griebe, Martin; Gass, Achim; Kern, Rolf; Hennerici, Michael G.; Szabo, Kristina (Cerebrovascular diseases, 2012)
Background: The human hippocampus can be affected in a large variety of very different neurological diseases, of which acute ischemic stroke, transient global amnesia, epilepsy, and limbic encephalitis are the most common. Less frequent etiologies include various infections and encephalopathy of different origins. Clinical presentation notably comprises confusional state, altered vigilance, memory deficits of various extent and seizures. While in hypoxic or hypoglycemic encephalopathy, clinical presentation and surrounding circumstances provide some clues to reach the correct diagnosis, in the above-listed more common disorders, signs and symptoms might overlap, making the differential diagnosis difficult. This review presents recent studies using the diffusion-weighted imaging (DWI) technique in diseases involving the hippocampus. Methods: References for the review were identified through searches of PubMed from 1965 to January 2011. Only papers published in English were reviewed. Full articles were obtained and references were checked for additional material where appropriate. Results: All pathologies affecting the hippocampus are associated with distinct lesion patterns on magnetic resonance imaging, and especially DWI has the ability to demonstrate even minute and transient hippocampal lesions. In acute ischemic stroke in the posterior cerebral artery territory, involvement of the hippocampal formation occurs in four distinct patterns on DWI that can be easily differentiated and correspond to the known vascular anatomy of the hippocampus. In the subacute phase after transient global amnesia (TGA), dot-like hyperintense lesions are regularly found in the lateral aspect of the hippocampus on DWI. The DWI lesions described after prolonged seizures or status epilepticus include unilateral or bilateral hippocampal, thalamic, and cortical lesions of various extent, not restricted to vascular territories. In limbic encephalitis, DWI lesions are only infrequently found and usually affect the hippocampus, uncus and amygdala. Furthermore, in some rare cases DWI lesions of different etiology may coexist. Conclusion: In patients with diseases affecting the hippocampus, DWI appears to be useful in differentiating between underlying pathologies and may facilitate a definite diagnosis conducive to an optimal treatment. With a careful clinical examination, experience with the interpretation of DWI findings and knowledge of associated phenomena, it is indeed possible to differentiate between ischemic, ictal, metabolic, and TGA-associated findings.
Published online: December 14, 2011
Gesehen am 10.04.2018